2019
DOI: 10.3390/sports7090203
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Fitness Improvements Found after 6-Months of High Intensity Functional Training

Abstract: While short-term high intensity functional training (HIFT) effects have been established, fitness improvements from program participation exceeding 16 weeks are unknown. This study examined the effectiveness of participation in HIFT through CrossFit. During 2013–2014, fitness performance testing was incorporated into an ongoing university CrossFit program. Participants included 45 adults (23 women, 22 men) with 0–27 months of HIFT experience (grouped into 0–6 months and 7+ months). Participants completed three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 47 publications
2
27
2
Order By: Relevance
“…Because the dose of betaine was similar to the one used in the above-mentioned studies (2.5 g/day), a possible explanation for the different results could be found in the training duration and intensity. Indeed, most of the studies on CrossFit© program required longer periods (>8 weeks) of treatment to observe significant changes in body composition [ 34 , 35 ]. Moreover, CrossFit© is a training approach characterized by the alternation of highly anaerobic and intense exercises, designed to increase muscle strength more than hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Because the dose of betaine was similar to the one used in the above-mentioned studies (2.5 g/day), a possible explanation for the different results could be found in the training duration and intensity. Indeed, most of the studies on CrossFit© program required longer periods (>8 weeks) of treatment to observe significant changes in body composition [ 34 , 35 ]. Moreover, CrossFit© is a training approach characterized by the alternation of highly anaerobic and intense exercises, designed to increase muscle strength more than hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…An a priori power analysis was computed using G*Power 3.1.9.4. Thus, a significant variable from a previous study (i.e., back squatting) was used for presenting improvement after performing HIFT [ 30 ]. The lowest significant effect size of back squatting (η 2 p = 0.55) was used for the power analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The participants completed three separate days of assessments across 10 fitness domains before and after participating in the program for 6 months. They found that HIFT improved several fitness parameters, including flexibility, power, muscular endurance, and strength 6 . Murawska-Cialowicz et al 7 also showed that there was an improvement in aerobic fitness after 3 months of HIFT training in women but not in men.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review, Haddock et al 5 suggests that HIFT increases aerobic fitness, strength, musculature, and endurance. Cosgrove et al 6 studied the influence of six months of HIFT on multiple fitness characteristics. The participants completed three separate days of assessments across 10 fitness domains before and after participating in the program for 6 months.…”
Section: Introductionmentioning
confidence: 99%